Dynamics of a magnetic monopole in matter, Maxwell equations in dyonic matter and detection of electric dipole moments - Artru, X.; Fayolle, D. (Вопросы атомной науки и техники, 2001)
For a monopole, the analogue of the Lorentz equation in matter is shown to be f = g(H-v×D). Dual-symmetric Maxwell equations, for matter containing hidden magnetic charges in addition to electric ones, are given. They apply as well to ordinary matter if the particles possess T-violating electric dipole moments. Two schemes of experiments for the detection of such moments in macroscopic pieces of matter are proposed.